Work Life Balance and Quality of Work Life as Predictors of Employee Performance with Job Satisfaction Mediation: (Study on Employees of PT. BPR BKK TASIKMADU (Perseroda) - Puthut Nurimbawono Hamiseno; Suhana (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of work-life balance (WLB) and quality of work-life (QWL) on employee performance with job satisfaction as a mediating variable. Respondents in this study were 116 employees of PT. BPR BKK Tasikmadu. Data processing was carried out using the SPSS program. The results of the study indicate that employee performance at PT BPR BKK Tasikmadu (Perseroda) is influenced by work-life balance. The results also show that the quality of work life has a significant positive effect on employee performance. Job satisfaction has a significant influence on improving employee performance. Satisfaction is able to mediate the effect of work-life balance and quality of work-life on employee performance. Theoretically, this study strengthens the theory of relationships between variables in this study. Practically, this study also provides input for the management of PT BRP BKK Tasikmadu (Perseroda) to implement various management policies to improve employee performance. This study has limitations and future research agendas.